Leadership, Work Environment, and Teacher Performance: The Mediating Role of Work Motivation in Indonesian Islamic High Schools - Fahlansyah; Misransyah Akos; Moh. Heru Budihantho; Nuril Mawaddah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
Teacher performance remains a central determinant of educational quality, particularly in Islamic secondary schools where organizational leadership and institutional climate play strategic roles. This study examines the structural relationships between leadership and work environment on teacher performance, with work motivation acting as an intervening variable. A quantitative explanatory research design was employed involving 80 teachers from two State Islamic Junior Secondary Schools (Madrasah Tsanawiyah Negeri) in Pelaihari District, Tanah Laut Regency. Data were collected using Likert-scale questionnaires and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that leadership and work environment do not have a significant direct effect on teacher performance. However, leadership significantly influences work motivation, and work motivation significantly affects teacher performance. Furthermore, work motivation mediates the relationship between leadership and teacher performance, while it does not significantly mediate the relationship between work environment and teacher performance. These results suggest that motivational mechanisms play a crucial role in translating leadership practices into improved teacher outcomes, whereas environmental factors alone are insufficient to directly enhance performance. This study contributes to educational management literature by clarifying the mediating function of work motivation within Islamic school contexts. The findings imply that strengthening motivational strategies through effective leadership practices is essential for improving teacher performance in public religious educational institutions.